Computational mechanisms of belief updating in relation to psychotic-like experiences - Fromm, Sophie Pauline; Wieland, Lara; Klettke, Arne; Nassar, Matthew R.; Katthagen, Teresa; Markett, Sebastian; Heinz, Andreas; Schlagenhauf, Florian (Frontiers in Psychiatry, 2023)
Introduction: Psychotic-like experiences (PLE) may occur due to changes in weighting prior beliefs and new evidence in the belief updating process. It is still unclear whether the acquisition or integration of stable beliefs is altered, and whether such alteration depends on the level of environmental and belief precision, which reflects the associated uncertainty. This motivated us to investigate uncertainty-related dynamics of belief updating in relation to PLEs using an online study-design. Methods: We collected a sample (n=300) of participants who performed a belief updating task with sudden change points and provided self-report questionnaires for PLE. The task required participants to observe bags dropping from a hidden helicopter, infer its position and dynamically update the belief about the helicopter’s position. Participants could optimize performance by adjusting learning rates according to inferred belief uncertainty (inverse prior-precision) and the probability of environmental change points. We used a normative learning model to examine the relationship between adherence to specific model parameters and PLE. Results: PLE were linked to lower accuracy in tracking the outcome (helicopter location) (β = 0.26±.11, p = .018) and to a smaller increase of belief precision across observations after a change point (β = -.003±.0007, p < .001). PLE were related to slower belief updating when participants encountered large prediction errors (β = -.03±.009, p = .001). Computational modelling suggested that PLE were associated with reduced overall belief updating in response to prediction errors (βPE = -1.00±.45, p =.028) and reduced modulation of updating at inferred environmental change points (βCPP = -.84±.38, p = .023). Discussion: We conclude that PLEs are associated with altered dynamics of belief updating. These findings support the idea that the process of balancing prior belief and new evidence, as a function of environmental uncertainty, is altered in PLE, which may contribute to the development of delusions. Specifically, slower learning after large prediction errors in people with high PLE may result in rigid beliefs. Disregarding environmental change points may limit the flexibility to establish new beliefs in the face of contradictory evidence. The present study fosters a deeper understanding of inferential belief updating mechanisms underlying PLE.